2006
DOI: 10.1196/annals.1369.024
|View full text |Cite
|
Sign up to set email alerts
|

Protection by GDNF and Other Trophic Factors Against the Dopamine‐Depleting Effects of Neurotoxic Doses of Methamphetamine

Abstract: Repeated methamphetamine (METH) administration to animals can result in long-lasting decreases in striatal dopamine (DA) content. It has previously been shown that glial cell line-derived neurotrophic factor (GDNF) can reduce the DA-depleting effects of neurotoxic doses of METH. However, there are several other trophic factors that are protective against dopaminergic toxins. Thus, the present experiments further investigated the protective effect of GDNF as well as the protective effects of several other troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Reduced neurotrophic support or deficiency in neurotrophin production might be involved in the pathogenesis of PD, proposing a notion that additional supplement of neurotrophic factors rescue the dopaminergic neurons and exhibit protective role in PD by halting or reversing degenerative processes. GDNF is one recommended among neurotrophic factor that plays an important role in survival of dopaminergic neurons, and many studies have suggested its beneficial effect in therapeutic treatment of PD patients [5,12,49]. In animal models of PD, neurotrophic factors prevented neurodegeneration and improved behavioral recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced neurotrophic support or deficiency in neurotrophin production might be involved in the pathogenesis of PD, proposing a notion that additional supplement of neurotrophic factors rescue the dopaminergic neurons and exhibit protective role in PD by halting or reversing degenerative processes. GDNF is one recommended among neurotrophic factor that plays an important role in survival of dopaminergic neurons, and many studies have suggested its beneficial effect in therapeutic treatment of PD patients [5,12,49]. In animal models of PD, neurotrophic factors prevented neurodegeneration and improved behavioral recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to attenuate the dopamine depletion promoted by methamphetamine when administered 1 day in advance [56]. In addition to GDNF, other members of the GDNF family, neurturin and artemin, when injected into the striatum 1 day before methamphetamine, were also found to protect the rat brain against methamphetamine-induced depletion of dopamine [20,57]. We observed an overall main effect of methamphetamine on GDNF expression in the frontal cortex and striatum, but the post hoc analysis did not demonstrate significant differences from the effect in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF activates several signalling cascades responsible for the regulation of cell survival, differentiation, proliferation, neurite outgrowth, and synaptic plasticity via the GDNF family receptor-α1 (GFR-α1) that can signal through RET [18]. Like BDNF, GDNF has been shown to protect rat dopaminergic neurons, e.g., against 6-hydroxydopamine toxicity [19], and intracerebral GDNF administration has been shown to reduce the dopamine-depleting effects of neurotoxic doses of methamphetamine in rats [20]. …”
Section: Introductionmentioning
confidence: 99%
“…This factor also has trophic effects on motor neurones [96] and has not been extensively investigated for its clinical potential in PD. The fourth member of the GFL family, artemin, has survivalpromoting effects on dopaminergic neurones in culture [98] and in vivo [99], and also has potent actions on sensory neurones of the dorsal root ganglia [98]. Like persephin, artemin has not progressed into clinical trials for PD; however it has been tested as a therapeutic for neuropathy [100].…”
Section: Effects Of Persephin and Artemin In Vitro And In Vivomentioning
confidence: 99%